Phillyrin Prevents Neuroinflammation-Induced Blood–Brain Barrier Damage Following Traumatic Brain Injury via Altering Microglial Polarization - Jiang, Qian; Wei, Ding; He, Xuejun; Gan, Chao; Long, Xiaobing; Zhang, Huaqiu (Frontiers in Pharmacology, 2021)
Background: Phillyrin (Phi) is the main polyphenolic compound in Forsythia suspensa. Recent studies have revealed that Phi has potent anti-oxidative and anti-inflammatory effects. However, whether Phi could relieve blood-brain barrier (BBB) damage following traumatic brain injury (TBI) remains unknown. Materials and methods: Lipopolysaccharide (LPS) was used for activating primary microglia, which were then treated with different doses of Phi or the peroxisome proliferator-activated receptor-gamma (PPARγ) antagonist (GW9662). CCK8 assay was used for evaluating cell viability, and the cytokines (including IL-1β, IL-6, TNFα, IL-4, IL-10, and TGFβ), microglial phenotypic markers (iNOS, COX2, and CD86 for “M1” polarization, Arg1, Ym1 and CD206 for “M2” polarization), and PPARγ, NF-κB were determined by RT-PCR, western blot, or cellular immunofluorescence. Primary cultured mouse brain microvascular endothelial cells (BMECs) were stimulated by the condition medium (CM) from microglia. The cell viability, angiogenesis and tight junction of BMECs were determined via CCK8 assay, tube formation assay, and western blot (for detecting MMP3, MMP9, ZO1, claudin-5, Occludin). Furthermore, the mouse TBI model was constructed and treated with Phi and, or GW6662). The BBB integrity was evaluated by HE staining, Evans blue staining and tissue immunofluorescence. Results: Phi markedly restrained the pro-inflammatory (“M1” state) cytokines and promoted anti-inflammatory (“M2” polarization) cytokines in LPS-mediated microglia. Phi mitigated “M1” polarization and promoted “M2” polarization of microglia via enhancing PPARγ and inhibiting the NF-κB pathway. The PPARγ antagonist GW9662 significantly repressed Phi-mediated anti-inflammatory effects. Meanwhile, Phi enhanced the viability, tube formation ability and cell junction of BMECs. In the TBI mouse model, Phi promoted the “M2” polarization while repressed the “M1” polarization of microglia. In addition, Phi reduced TBI-mediated BBB damage. However, the protective effects of Phi were reversed mainly by GW9662 treatment. Conclusion: Phi prevents BBB damage via inhibiting the neuroinflammation of microglia through the PPARγ/NF-κB pathway, which provides a potential therapeutic drug against TBI.